2021
DOI: 10.1186/s12301-021-00122-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of prostate volume with severity of lower urinary tract symptoms as measured by international prostate symptoms score and maximum urine flow rate among patients with benign prostatic hyperplasia

Abstract: Background The aim of the study is to find the correlation between the prostate volume and severity of lower urinary tract symptoms (LUTS) as measured by international prostate symptoms score and maximum urine flow rate among patients with benign prostatic hyperplasia (BPH). Methods The study was a prospective correlational study conducted between June 2016 and November 2017. A total of 290 patients who presented with LUTS suggestive of BPH and sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
2
14
2
Order By: Relevance
“…6 There was no correlation between the prostate volume and IPSS scores unlike this study in Africans. 5 In a study by Azhar et al, there was a statistically significant difference between the grading of prostate by trans abdominal ultrasound and IPSS scores similar to the results of this study. 7 A study by Awaisu et al had shown a positive and significant correlation of between the prostate volume and IPSS scores.…”
Section: Disussionsupporting
confidence: 90%
See 3 more Smart Citations
“…6 There was no correlation between the prostate volume and IPSS scores unlike this study in Africans. 5 In a study by Azhar et al, there was a statistically significant difference between the grading of prostate by trans abdominal ultrasound and IPSS scores similar to the results of this study. 7 A study by Awaisu et al had shown a positive and significant correlation of between the prostate volume and IPSS scores.…”
Section: Disussionsupporting
confidence: 90%
“…3 A study by Awaisu et al had noted that, the mean age of the patients was 64.22 years. 5 Increased frequency was the main lower urinary tract symptom in this study followed by urgency, incomplete emptying, nocturia, poor streaming and straining.…”
Section: Disussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Earlier studies on this topic have demonstrated variable results. [32][33][34][35][36][37][38] Additional research in this area is needed to determine if certain clinical or patient characteristics may in uence the relationship between PV and IPSS.…”
Section: Discussionmentioning
confidence: 99%